Euglesa kolymensis Bespalaya, Aksenova & Bolotov 2024, sp. nov. ... - Bespalaya, Yulia V.; Vinarski, Maxim V.; Aksenova, Olga V.; Babushkin, Evgeniy S.; Gofarov, Mikhail Yu.; Kondakov, Alexander V.; Konopleva, Ekaterina S.; Kropotin, Alexander V.; Mabrouki, Youness; Ovchankova, Nadezda B.; Palatov, Dmitry M.; Sokolova, Svetlana E.; et al. (Zenodo, 2023)
Euglesa kolymensis Bespalaya, Aksenova & Bolotov sp. nov. (Fig. 11A) Zoobank number: urn:lsid:zoobank.org:act: BDC94015-12D0- 42CB-B21E-F7C950E94EFD. Type series: The holotype is deposited in RMBH (accession number: MSph-787). The type series includes one holotype. Type locality: Russia: Yakutia, Srednekolymsk, lake next to the oil depot, Kolyma River Basin, [67°27 ʹ 29″N 153°42 ʹ 22″E], 25. VI.2021, Sokolova & Zubrii leg. Etymology: This species is named after the Kolyma River. Description: Shell round-oval in shape, its length is 4.7 mm (Fig.11A). The beaks are rounded and slightly protruding, somewhat shifted to the posterior edge of the shell (Fig.11A). The cardinal tooth of the right valve slightly curved has a thickening at the ends, the posterior end is branched. The cardinal teeth of the left valve are straight parallel to each other (Fig. 12C). The inner cardinal tooth of the left valve is thickened. Distribution: Eastern Siberia, Kolyma River Basin. Comments: The 16S and 28S rRNA sequences ... : Published as part of Bespalaya, Yulia V., Vinarski, Maxim V., Aksenova, Olga V., Babushkin, Evgeniy S., Gofarov, Mikhail Yu., Kondakov, Alexander V., Konopleva, Ekaterina S., Kropotin, Alexander V., Mabrouki, Youness, Ovchankova, Nadezda B., Palatov, Dmitry M., Sokolova, Svetlana E., Shevchenko, Alexander R., Travina, Oksana V., Taybi, Abdelkhaleq F., Soboleva, Alena A., Zubrii, Natalia A. & Bolotov, Ivan N., 2024, Phylogeny, taxonomy, and biogeography of the Sphaeriinae (Bivalvia: Sphaeriidae), pp. 305-338 in Zoological Journal of the Linnean Society 201 (2) on pages 323-326, DOI: 10.1093/zoolinnean/zlad139, http://zenodo.org/record/13220074 ...